1996
DOI: 10.1074/jbc.271.9.4718
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Topa Quinone Cofactor in Bacterial Amine Oxidases

Abstract: Resonance Raman spectroscopy is an excellent technique for providing structural information on the 2,4, 5-trihydroxyphenylalanine quinone (TPQ) cofactor in copper-containing amine oxidases. This technique has been used to investigate the copper- and O2-dependent biosynthesis of the TPQ cofactor in phenylethylamine oxidase (PEAO) and histamine oxidase from Arthrobacter globiformis. Incubation of the holoenzyme in H218O causes frequency shifts at 1684(-26) cm-1 in PEAO and at 1679(-28) cm-1 in histamine oxidase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 19 publications
7
67
0
Order By: Relevance
“…TPQ biogenesis is a Cu II -dependent process that consumes two molecules of O 2 and involves the insertion of two oxygen atoms into the phenolic ring of an active site tyrosine (Scheme B). Although isotopic labeling studies (to determine whether the TPQ oxygens derive from O 2 or solvent) are not feasible due to rapid exchange, crystallographic, mutant, and model studies have shown that the AO biogenesis reaction occurs through one monooxygenation and one hydration step (Scheme B). However, little is known about the mechanistic nature of these steps or the geometric and electronic structure adopted by the active site copper prior to or during the biogenesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…TPQ biogenesis is a Cu II -dependent process that consumes two molecules of O 2 and involves the insertion of two oxygen atoms into the phenolic ring of an active site tyrosine (Scheme B). Although isotopic labeling studies (to determine whether the TPQ oxygens derive from O 2 or solvent) are not feasible due to rapid exchange, crystallographic, mutant, and model studies have shown that the AO biogenesis reaction occurs through one monooxygenation and one hydration step (Scheme B). However, little is known about the mechanistic nature of these steps or the geometric and electronic structure adopted by the active site copper prior to or during the biogenesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaquinone (DPQ) is proposed to be the common intermediate during the biogenesis of TPQ and LTQ, where the 1,4-addition of either water or the ε-amino side chain of a peptidyl lysine residue to DPQ yields TPQ or LTQ, respectively (13,14) (Figure 2). A careful inspection of the reaction product of TPQ biogenesis in the presence of H 2 18 O and 18 O 2 by resonance Raman spectroscopy revealed that the C2 oxygen of TPQ is from solvent water, rather than O 2 (17). In the same study, substantial electron delocalization between the C2 and C4 oxygens of the TPQ cofactor was observed, whereas the C5=O bond had more carbonyl character.…”
Section: Introduction and Reaction Mechanism Of Tyrosine-derived Quinmentioning
confidence: 99%
“…These components, in the absence of other factors, including reducing equivalents, are sufficient for the conversion of tyrosine to TPQ in Vitro (6). Mechanisms involving a copper hydroperoxide (7) or tyrosyl radical (8) have been put forth; however, neither mechanism has been supported by experimental evidence nor is there a clear understanding as to which residues may be critical for biogenesis to occur.…”
mentioning
confidence: 99%